Factors affecting union participation among employees at hotels in Kota Kinabalu, Sabah - Enny Marlinah Manggor (2014)
Low pay in the hotel and catering industry is generally held to create a culture of instrumentalism amongst many employees. Therefore, employees need a strong voice to articulate what workers need at their working conditions. This is where trade union can offer a respected representative at workplace to negotiate with employer. However, recently, declining in union density worldwide seems to signify a weakening of their influence. This study attempt to investigate the relationship between employee needs affecting union participation, union role played that affect union participation and employer attitude towards union that affect employee decision to participate in union. A total of two hundred questionnaires were sent to the hotel. To analyses the relationship factors that influence union participation, multiple regression analysis was run. From the data analysis, two hypotheses was accepted, which are reason of employee belong to union and union role, while the other one hypotheses was rejected which is employer attitude towards union.